Peningkatan Kecerahan Warna Benih Ikan Sumatra (Puntius Tetrazona) Melalui Pengkayaan Tepung Wortel (Daucus Carota) Dalam Pakan di Griya Sejahtera, Tanjung Pering, Ogan Ilir - Cahya Mukti, Retno; Rahmadania, Ella; Dahnia, Lilis; Armelia Putri, Trida; Pustika, Rita; Sry Lidya, Jessica; Husaini, Fahrian; Nugroho, Aji (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Mukti, RC., Rahmadania, E., Dahnia L., Putri T.A., Pustika. R., Lidya, J.S., Husaini, F., Nugroho, A. (2023). Increasing the color brightness of sumatra fish seeds (Puntius Tetrazona) through enriching carrot flour (Daucus Carota) in feed at Griya Sejahtera, Tanjung Pering, Ogan Ilir. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp.185-191). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Sumatran fish (Puntius tetrazona) is a type of ornamental fish native to Indonesia which is often found in the public waters of the islands of Sumatra and Kalimantan. This ornamental fish has an attractive color and body shape and has high economic value. The color of the fish can be improved by adding feed ingredients. containing carotenoids. The aimed of this research is to determine the increase in color brightness of Sumatran fish (Puntius tetrazona) by adding carrot flour to the feed. The method used is an experimental method starting from container preparation, feed testing, fish rearing, data analysis and water quality. The results of research on increasing the color brightness of Sumatran fish (Puntius tetrazona) by adding carrot flour to the feed gave positive results, namely increasing the color brightness of Sumatran fish by 5.86, absolute weight growth of 0.16 g, absolute length growth of 0.21 cm, feed efficiency 10% and 100% survival. These results show that the value of increasing color brightness in the carrot flour addition treatment is better, namely 5.86, while the increasing color brightness in the control treatment is 3.66 and the addition of 10% carrot flour can be applied by ornamental fish farmers in Sumatran fish feed to obtain better results.